Policies and strategies for promoting entrepreneurship and enterprise development. - Morato, Eduardo A., Jr. (Animo Repository, 2004)
The dissertation paper on Policies and Strategies for Promoting Entrepreneurship and Enterprise Development derives its impetus from the author's desire to contribute to the Philippine government's effort to generate wealth and alleviate poverty. To achieve this aim, the paper postulates that the most appropriate strategic intervention is enterprise creation and propagation through policies and programs that stimulate entrepreneurship. As a free enterprise economy, the primary engine of growth in the Philippines is private sector investments. Business enterprises generate tremendous economic value added and employment Given this premise, the key research question posted by the researcher is what motivates, encourages and influences entrepreneurs to set up and grow and their businesses? In answering the question, the researcher posits that there are seven general factors which affect entrepreneurship and enterprise development. There are the: (1) Macroenvironmental Political, Economic and Social Factors; (2) the Cost of Doing Business; (3) the Cost of Producing and Delivering Services; (4) Market Opportunities;(5) Industry Clustering; (6) Ancillary, Related and Support INdustries; and (7) the Entrepreneurs themselves.The dtssertation reviews relevant literature which establish the linkages among economic development, employment, poverty alleviarion and entrepreneurship. The research highlights findings on what causes poverty and what macro and micro* level conditions propel economic growth. The literature review reveals two major schools of thought on how to alIeviate poverty: the Economic Growth Model and the Pro-Poor Model. The former relies on the trickle-down of effects of economic growth while the latter insists on dedicated anti-poverty programs. The paper integrates the tvo schools of thought by stressing the importance of national macro policies in spurring economic growth in tandem with micro-level pro-poor investments. The paper likewise establishes the impact of industry clusters in creating enterprises and sharpening industry competitiveness. The dissertation bringsthe discussion to the Philippine context by assessing the country's economic performance and the policies and programs it has adopted for wealth creation and poverty alleviation over the last five decades. The Philippine policy regimes are articulated in five distinct stages. The first three stages have been inward-looking and protectionist in orientation. The last two stages have been outward-looking and biased towards free trade. The latter has proven to be more conducive to enterprise development, although certain sectors and industries have been found uncompetitive and vulnerable to the '·external shocks" of globalization. The study of Philippine policies and strategies has also unearthed biases against agriculture and rural development and revealed basic deficiencies in economic, social and political structures.The dissertation shows the correlation between the establishment of new enterprises and employment on one hand and gross domestic product on the other hand. By identifying relatively stable or unstable periods during the different presidential regimes, the research concludes that the political, social and economic environment prevailing during any one period significantly influences the formation of new enterprises. The research scans the major public programs on enterprise development and profiles the various government agencies which deliver technology, marketing, training, financing and other services to business firms. The paper notes that the government is beginning to recognize the benefits of convergence on industry clusters and economic zones. The launching of the National SME Agenda pushes convergence to the forefront of Philippines enterprise development strategy. The research has chosen four industry clusters (tourism, jewelry, footwear and furniture) in four different locations (Mactan, Meycauayan, Marikina and Pampanga, respectively) to extract insights on the causes and effects of enterprise concentrations in specific areas. To augment the four industry studies, the researcher undertook seventeen case studies on entrepreneurs and enterprise promoters in the same clusters. The industry and case studies confirm that clusters accelerate business formations, enhance productivity and innovation, produce synergies in cost competitiveness, marketing, production, research and development and provide easier access to public services. The studies also highlight four significant variables in motivating entrepreneurs aside from earning a livelihood or generating profits. These four are: Connections (relatives, friends), Competence professional background), Cluster osmosis (experience and exposure to the industry) and Character (personal drive, talents and expertise). The case studies generated thirty-five facilitative and hindering factors in promoting entrepreneurship, which 35 factors were subsequently classified by the researcher according to the seven general factors identified.The researcher conducted a nationwide survey involving 180 entrepreneurs in four high growth regions and two low growth regions in the Philippines to determine the importance of the seven general factors and fifty-nine specific factors. The 59 factors were culled from an earlier exploratory survey of twenty-four entrepreneurs in Metro Manila. The dissertation derives an Expanded Enterprise Development Framework from the survey based on what the 180 entrepreneurs deemed were very important to them in terms of top box scores given. The framework maintains that the entrepreneur's internal resources and competencies are the starting point. The external motivator for entry or expansion in business is the macro environment's social and economic factors. If .found conducive for business, the entrepreneur sets up the enterprise, where the main concern becomes the cost of production inputs: raw materials and labor. In terms of sourcing these inputs, the bigger issue is the availability of raw materials/goods from the industry's suppliers. Aside from the cost of producing goods and delivering services, the enterprise must keep two vital costs of doing business down: infrastructures and utilities, and logistics. Enterprises thrive well when related, ancillary and support industries complete the industry supply and market chains. Enterprises and industries temper or accelerate their growth plans based on the general economic outlook and market demand trends. The growth in local and export markets fuel the engines of enterprises, motivating entrepreneurs to expand and intensify their efforts.The survey design incorporates several independent variables which segment the enterprises: (1) in the high growth regions versus the low growth regions; (2) located in clusters or not located in clusters; (3) engaged in manufacturing, trading or services; (4) that are micro or small; (5) that are new (two years operational and below) or old (more than two years in existence). The answers given by the different segments of enterprises, which are significantly different from one another, are analyzed by the researcher to determine which specific factors should be given policy and program priority. The researcher has discovered that the 180 enterprises could be classified into two major groups. The first one is composed of high growth, clustered, small and old enterprises. The second group is comprised of low growth, not clustered, micro and new enterprises. The second group tends to give more importance to a greater number of specific factors than the first group, suggesting that they need more support and encouragement because they are less endowed with resources, expertise, experience and linkages.The research observes that none of the specific factors in the first group crossed over to the second group or vice versa. This validates the rationale for grouping the 180 enterprises according to the independent variables enumerated. The dissertation shows that the macroenvironmental social factors are deemed more important by the second group than the first, while the political factors affect the first group more than the second. The economic factors have mixed effects. As for the enterprises in manufacturing, trading and services, the researcher identifies their foremost concerns. Manufacturers tend to focus on the basic costs of producing goods, equipment/logistics costs, subcontracting and outsourcing, the · supply chain and clustering. Trading firms emphasize informal costs, trade policies, exchange rates, logistics and supplies, market access, clustering and infrastructures. Service enterprises cite government laws, rules and regulations, lack of jobs available and infrastructures as more important to them compared to the other two types of enterprises. Finally, the research summarizes the findings of each chapter and recommends policies and strategies based on the conclusions made. An integration of the seven general factors (Macroenvironment, Cost of Doing Business, Cost of Producing and Delivering Services, Market Opportunities, Industry Clustering, Related, Ancillary and Support Industries and Entrepreneurs) caps the dissertation by triangulating the three research methodologies of: (I) literature review· and analyses of secondary data; (2) industry and case studies; and (3) survey of entrepreneurs. For each general factor, the researcher summarizes the recommended policies and strategies that would promote entrepreneurship and encourage enterprise development. The dissertation provides the following major policy and strategy recommendations: 1. The basic condition for enterprise development is the presence of a safe, secure and stable macroenvironment that inspires investor confidence.2. Entrepreneurs want less government when it comes to the free flow of business transactions but more government when it pertains to the cost of Doing Business meanmg the provision of vital infrastructures, utilities, logistics and business support.3.Strategic priority should be accorded to Industry Clusters where the government should pursue a Convergence strategy by completing the s·upply and market Chains.4. Strategic priority should be given to industries which generate high multiplier effects, high contribution to value added and extensive employment.5. Industries should be prioritized according to their ability to compete globally on the attractiveness of their local markets.6. Macro level policies should be complemented by micro industry interventions to enhance the interplay of the seven general factors which promote entrepreneurship. In this context, the government should build up the capabilities of public and private institutions which provide critical services to industries and enterprises.7. The government should design, ·encourage and promote entrepreneurship and enterprise development programs revolving around the provision of: equity and quasi-equity financing; education, training and apprenticeship; ecozones, industry linkages and enterprise incubators; marketing and promotional assistance; technology upgrading and technical assistance; transport and warehousing facilities; product research, design and development services.8. The government should adopt the Expanded Enterprise Development Framework proposed in the dissertation because it highlights the most important variables which influence, motivate and encourage entrepreneurs.9. The government should follow a more interventionist and developmental approach in low growth regions and a more facilitative and enabling approach in high growth regions. Necessarily, newer, smaller and unclustered enterprises require the integrated delivery of assistance packages.